PENGARUH FAKTOR-FAKTOR RISIKO PENUAAN DINI DI KULIT PADA REMAJA WANITA USIA 18-21 TAHUN - Dewiastuti, Marlina; Hasanah, Irma Fathul (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2016)
Skin aging process is a dynamic process. Skin aging process causes histologic change in skin layer. There are 2 factors causing skin aging process, intrinsic factor (nutritional status) and extrinsic factor (UV light).Tis research was conducted in a population of medical students of UPN Veteran Jakarta. The objective of this study was to ascertain prevalence of skin aging process and whether there was a relationship between the intrinsic and extrinsic factors and skin aging process. The design in this study was a cross-sectional study of the 136 research subjects. The collected data were analyzed by univariate, bivariate, and multivariate analysis. The incidence of skin aging process is 57.35%. Chi-square test showed that there was a relationship between the application of sunscreen and skin aging process (p = 0.001). There was no signifcant relationship between nutritional status (p=0,246) and skin aging process. From that result, skin aging process has occurred in late adolescent and most inﬂuence factor is application of sunscreen.